Are Gender Differences Exhibited in the Self-directed Learning Experiences of Prostate and Breast Cancer Patients? - Kathleen Rager (Adult Education Research Conference, 2007)
A secondary analysis was conducted using data from two qualitative studies regarding the self-directed learning of prostate and breast cancer patients.Of interest were differences that appear to relate to gender. The findings indicate the men and women differed in regard to privacy, seeking connections, handling emotions, and perspectives on the personal impact of their self-directed learning and cancer experiences.